Root growth in wheat and rice seeds treated with Bio-activator - Macedo, Willian Rodrigues; Castro, Paulo Roberto de Camargo e (Comunicata Scientiae, 2012)
This research aimed to evaluate the initial root growth of wheat and rice subjected to increasing doses of thiamethoxam, the doses were 0; 8.75; 17.5; 35 e 70 g a.i. per 100 kg of seeds for wheat and 0; 17.5; 35; 70 e 105 g a.i. per 100 kg of seeds for rice, applied in seeds and to growing in mini-rhizotrons placed at greenhouse. Daily evaluations began after the emergence of the root, for ten days. The bio-activator showed great variability in the response of daily root growth, when the effect was significant the increasing doses led to length reductions.